EVALUATION ON DHARMA SASTRAS AND WOMEN WITH SPECIAL FOCUS TO ANCIENT AND MEDIEVAL INDIA - Ghosh, Subrata Kumar; Varma, Vandana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The sacrificial ritualism of the Vedas grew to be defined and systematized, obviously because it was widely adopted, and this is evident in the socio-religious culture that can be inferred from the later Vedic literature, the Samhitas of Yajus and Sama-vedas and the Brahmana and Aranyaka texts. However, there is no doubt that it was also eventually losing its hold on the populace. In this article, evaluation on dharma sastras and women with special focus to ancient and medieval India has been discussed.